High Frequency of Plantlet Regeneration and Multiple Shoot Induction From Leaf and Stem Explant of Citrullus Colosynthis (L.) Schrad, An Endangered Medicinal Cucurbit - R. SAVITHA; T. SHASTHREE; SUDHAKAR; B.MALLAIAH (International Journal of Pharma and Bio Sciences, 2010)
Efficient plant regeneration via organogenesis was established using leaf and stem explant. Callus cultures from the leaf and stem explants were tested for growth and organogenic capacity on MS medium fortified with different concentrations and combination of 2,4-D with BAP and 2,4-D with TDZ. The maximum morphogenic callus induction rate (65%) was observed from leaf explant by culturing in MS medium supplemented with 1.5 mg/l 2,4-D + 1.0 mg/l BAP when compared to 2.0 mg/l 2,4-D + 1.0 mg/l TDZ (50%). High frequency shoot regeneration (75%) from leaf derived callus was observed on MS medium supplemented with 2.5 mg/l 2,4-D and 0.5 mg/l TDZ. At the end of 3 weeks the regenerated shoots were transferred on the same medium (MS + 2.5 mg/l 2,4-D + 0.5 mg/l TDZ) for further proliferation and elongation. The regenerated shoots were rooted with high frequency (60%) in MS medium supplemented with 1.5 mg/l IBA when compared to other auxin NAA. The in vitro raised plantlets were successfully established in green house and transplanted to natural conditions with 70% survival.